Assessing the Dynamics of Urban Growth and Land Use Changes in Jeli Using Geospatial Technique (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
Land use change pattern in Jeli is been given a focus as part of tool for land planning and development. An increasing of population in Jeli make this study is relevant to aid an understanding on land use changes in this area due to the demanded for development and rapid land utilisation. Land use change pattern can be obtained via geospatial technique by Geographical Information System (GIS) together with satellite imagery analysis. In this study, land use maps produced from supervised classification using maximum likelihood algorithm give a high accuracy of 92.05%. From classified land use images, urban expansion index (SI) were then calculated from year 1984 to 2012. Pearson’s correlation analysis discovered a strong negative correlation between forest and agricultural areas which reflected that with increased of agriculture area, forest reserve was found depleted. The SI of Jeli showed a low to rapid growth in 1994 and 1997 to 2012 respectively. The study reflected the progressive development in Jeli promotes sustainable usage of forest area when effort of reforestation was carried out forming a co-existence land use category between forest and agriculture.
Keywords: Urban growth; land use changes; geaospatial; Geographic Information System; remote sensing